Mobil Teknolojilerin Mevcut Kullanımlarına Yönelik Görüşler ile Öğretim Amaçlı Kullanımlarına Yönelik Yönelimler Arasındaki İlişki. - Çakıroğlu, Ünal; Gökoğlu, Seyfullah; Erdemir, Turgay; Öztürk, Mucahit (XI. International Computer & Instructional Technologies Symposiun. Gaziantep, Türkiye., 2012)
Mobil teknolojilerin öğretim amaçlı kullanımı ile ilgili olan araştırmalarda, bu tür öğrenme ortamlarını oluşturacak olan öğretmenlerin önemli rolleri olduğu ve bu konudaki düşüncelerinin mobil cihazların öğrenme ortamlarına entegrasyonunda değerli görüldüğü ortaya konulmuştur. Bu kapsamda bilişim teknolojileri öğretmenlerinin mobil cihazlar ile ilgili düşünceleri ve bu cihazları kullanım durumları, bu cihazların öğretim amaçlı kullanılabilirliği ve okullara entegrasyonunun kolaylaşması açısından önemlidir. Bu doğrultuda bu araştırma “Öğretmen adaylarının mobil teknolojileri mevcut kullanım durumları ile öğretmen oldukları zaman kullanma yönelimleri arasındaki ilişki nedir?" problemi üzerinde yoğunlaşmaktadır. Çalışmada veriler Bilgisayar ve Öğretim Teknolojileri Eğitimi bölümü 3. ve 4. Sınıfta okuyan 112 öğrenciye uygulanan anketlerle toplanmıştır. Elde edilen veriler analiz edildiğinde, mobil teknolojilerin mevcut kullanım durumları ile öğretim amaçlı kullanım durumları arasında ve mevcut kullanım durumları ile gelecekteki kullanım niyetleri arasında pozitif yönde güçlü bir ilişki olduğu ortaya çıkmıştır. Buradaki mevcut kullanım, gelecekteki kullanım veya mevcut kullanım, öğretim amaçlı kullanım ilişkileri teknoloji kabul modelindeki bileşenler çerçevesinde açıklanabilmektedir. Computer teachers’ opinions about mobile devices and their use of these devices are of significance in terms of facilitating their instructional availability and integration into classrooms. In this respect, the study focuses on the question, “What is the relationship between pre-service teachers present state of using mobile technologies and their tendency towards using these technologies after they become teachers?” The data was gathered through questionnaires completed by 112 third and fourth grade students at the Department of Computer and Instructional Technologies Education. Following the analysis of the data obtained, a strong positive relationship between the participants’ present state of using mobile technologies and their state of instructional and between their present use of such technologies and respondents’ intentions to use them in the future use was observed. As a result, relationships between present use and future use, or present use and instructional purposes can be explained within the context of usefulness, ease of use, and intentional components perceived in the technology acceptance model. Computer teachers’ opinions about mobile devices and their use of these devices are of significance in terms of facilitating their instructional availability and integration into classrooms. In this respect, the study focuses on the question, “What is the relationship between pre-service teachers present state of using mobile technologies and their tendency towards using these technologies after they become teachers?” The data was gathered through questionnaires completed by 112 third and fourth grade students at the Department of Computer and Instructional Technologies Education. Following the analysis of the data obtained, a strong positive relationship between the participants’ present state of using mobile technologies and their state of instructional and between their present use of such technologies and respondents’ intentions to use them in the future use was observed. As a result, relationships between present use and future use, or present use and instructional purposes can be explained within the context of usefulness, ease of use, and intentional components perceived in the technology acceptance model.
PRESERVICE COMPUTER TEACHERS’ TENDENCIES TOWARDS USE OF MOBIL TECHNOLOGIES: RELATIONS AMONG PRESENT USE AND FUTURE TENDENCIES
Keywords: Mobil Teknolojiler, Teknoloji Kabul Modeli(TKM), Bilişim Teknolojileri Öğretmenleri; Mobile Technologies, Technology Acceptance Model, Computers Teachers